A systematic review of newborn health interventions in humanitarian settings. Issue 7 (1st July 2022) - Rodo, Mariana; Duclos, Diane; DeJong, Jocelyn; Akik, Chaza; Singh, Neha S
Abstract : Background: Almost half of the under-5 deaths occur in the neonatal period and most can be prevented with quality newborn care. The already vulnerable state of newborns is exacerbated in humanitarian settings. This review aims to assess the current evidence of the interventions being provided in these contexts, identify strategies that increase their utilisation and their effects on health outcomes in order to inform involved actors in the field and to guide future research. Methods: Searched for peer-reviewed and grey literature in four databases and in relevant websites, for published studies between 1990 and 15 November 2021. Search terms were related to newborns, humanitarian settings, low-income and middle-income countries and newborn health interventions. Quality assessment using critical appraisal tools appropriate to the study design was conducted. Data were extracted and analysed using a narrative synthesis approach. Results: A total of 35 articles were included in this review, 33 peer-reviewed and 2 grey literature publications. The essential newborn care (ENC) interventions reported varied across the studies and only three used the Newborn Health in Humanitarian Settings: Field Guide as a guideline document. The ENC interventions most commonly reported were thermal care and feeding support whereas delaying of cord clamping and administration of vitamin K were the least. Training of healthcare workers was the most frequent strategy reported to increase utilisation. Community interventions, financial incentives and the provision of supplies and equipment were also reported. Conclusion: There is insufficient evidence documenting the reality of newborn care in humanitarian settings in low-income and middle-income countries. There is a need to improve the reporting of these interventions, including when there are gaps in service provision. More evidence is needed on the strategies used to increase their utilisation and the effect on health outcomes. PROSPERO registration number: CRD42020199639.